2016
DOI: 10.3390/ijms17030294
|View full text |Cite
|
Sign up to set email alerts
|

The Human Host Defense Ribonucleases 1, 3 and 7 Are Elevated in Patients with Sepsis after Major Surgery—A Pilot Study

Abstract: Sepsis is the most common cause of death in intensive care units and associated with widespread activation of host innate immunity responses. Ribonucleases (RNases) are important components of the innate immune system, however the role of RNases in sepsis has not been investigated. We evaluated serum levels of RNase 1, 3 and 7 in 20 surgical sepsis patients (Sepsis), nine surgical patients (Surgery) and 10 healthy controls (Healthy). RNase 1 and 3 were elevated in Sepsis compared to Surgery (2.2- and 3.1-fold,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 48 publications
1
20
0
4
Order By: Relevance
“…Specifically, we report for the first time to our knowledge that the levels of RNH1, the endogenous inhibitor of RNase 1, are significantly elevated on the day of diagnosis and 3 days after diagnosis of sepsis ( Figure 1A). We have also recently reported an increased serum expression of RNase 1 at the onset of sepsis (22). RNH1 specifically binds to RNase 1 and inhibits its activity (20).…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Specifically, we report for the first time to our knowledge that the levels of RNH1, the endogenous inhibitor of RNase 1, are significantly elevated on the day of diagnosis and 3 days after diagnosis of sepsis ( Figure 1A). We have also recently reported an increased serum expression of RNase 1 at the onset of sepsis (22). RNH1 specifically binds to RNase 1 and inhibits its activity (20).…”
Section: Discussionmentioning
confidence: 72%
“…RNH1 is elevated in serum of septic patients. We recently reported that serum levels of RNase 1 are substantially elevated in the early phase of sepsis (22). Because RNH1 inhibits the enzymatic activity of RNase 1, serum levels of RNH1 in septic patients (n = 21) were investigated on the day of and 3 days after diagnosis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the detection of Apo-A1 90 , EPO 91 , GDF-11 92 , RNase-1 93 (ELISA Cloud-Immunoassay, Houston, USA) and HIF-1α 94 (RayBio, Georgia, USA) avidin-conjugated horseradish peroxidase was supplemented. For the detection of GLP-1 95 (Abcam, Cambridge, UK) an antibody cocktail consisting of a capture and a detector antibody was supplemented.…”
Section: Methodsmentioning
confidence: 99%
“…Наиболее представленными в человеческой сыворотке в количественном отношении являются лизоцим (2800±800 нг/мл) [7], РНКазы (2200±400 нг/мл) [10] и дермцидины (2100±100 нг/мл) [11]. Их концентрации в данном ликворе вполне соотносятся с их минимальными ингибирующими концентрациями в отношении C. albicans, что дает основание считать именно эти АМП отвечающими за противокандидозную активность сыворотки.…”
Section: р е з у л ьт а т ы и о б с у ж д е н и еunclassified